Hyperlipidemia and apolipoprotein E are associated with intraocular pressure of thyroid-associated ophthalmopathy in a Chinese population: a cross-sectional study - Chen, Yu; Qi, Xin; Wang, Jingya; Xu, Huayang; Sun, Yushi; Wang, Ling; Zhou, Xingchen; He, Mingqian; Zhao, Jiarui; Zhang, Jinbo; He, Hairong; Guo, Hui; et al. (Frontiers in Endocrinology, 2024)
Objective: to explore the clinical characteristics of Thyroid-associated ophthalmopathy (TAO) with hyperlipidemia and identify the key lipid indicator.Methods: TAO patients were recruited in this study and divided into 2 groups based on the presence of hyperlipidemia. The TAO patients with hyperlipidemia were furtherly grouped based on the type of hyperlipidemia. Basic and clinical information of patients were collected ， and comparisons between the groups were carried out. Correlation analyses, regression analyses and stratified analysis were performed to assess the correlations and relationship of serum lipids and ophthalmic assessments.Results: A total of 273 TAO patients were recruited, including 158 patients with hyperlipidemia and 115 patients without hyperlipidemia. A high intraocular pressure (IOP) was exhibited in the patients with hyperlipidemia, especially with mixed hyperlipidemia. Spearman correlation analysis and partial correlation analysis showed that the apolipoprotein E (Apo E) was positively related with IOP levels, after controlling the confounding factors, including age, gender, BMI, smoking history, T3 and TSH.Moreover, multiple linear regression obtained a regression equation including ApoE, gender, age and BMI, and showed that elevated ApoE levels was associated with elevated IOP[β:0.072, 95% 2 confidence interval (CI):0.037-0.155, P=0.030]. Stratified analysis highlighted the impact of ApoE on IOP in younger patients (≤48 years), female patients, patients with normal BMI (＜24kg/m 2 ) and patients with shorter course of ophthalmopathy (≤6 months).Conclusion: Overall, we demonstrated a higher IOP levels in patients with hyperlipidemia, especially those with mixed hyperlipidemia. Notably, higher ApoE was identified as an independent risk factor for higher IOP. This finding confirmed the close relationship between TAO and lipid metabolism, and provides a new insight for the pathogenesis research and the long-term management for TAO.